Recent impacts of copyright law upon distance education - Sue French (Flexible Learning Association of New Zealand, 2012)
The requirements of Copyright law continue to be influential in the development of distance education teaching courses. This paper examines various areas of the law and analyses their practical effect upon the teaching of distance education in New Zealand. Certain recent developments in international copyright law are discussed and an assessment made of their possible effect on domestic law.